Higher Education Challenges in the Era of Covid-19, from the Perspective of Educators and Students (Ghana, Georgia and Pakistan Cases) – A literature Review - Paul Kwame Butakor; Tamar Kakutia; Syed Mir Mucammad Shah; Elena Hunt (European Scientific Journal, ESJ, 2022)
For the last three years, the entire world has faced a colossal phenomenon - the covid-19 pandemic. All sectors and areas of life have been affected, forcing rapid and radical changes towards adaptation in its wake. Inevitably, the unexpected pandemic’s mark and impact on education is more severe and longer lasting than imagined. It disrupted education provision at an unprecedented scale. This article is intended as a review of literature on the experience of different countries and education systems during the Covid-19 pandemic. Based on the analysis of the existing literature and research on this issue, from the perspective of educators and students, including the experience of different countries around the world, the pandemic has had a great impact on higher education and pushed it to digital transformation, implicitly overcoming important challenges. The review uses particular examples of higher education in the era of Covid-19 in Georgia, Ghana and Pakistan, exposing measures taken to continue educating in spite of the pandemic. However challenging this phenomenon proved to be, it equally gave way to enormous opportunities for creativity within progress. Discussed are barriers that students and academics faced during online teaching-learning, the pros and cons of online teaching-learning, as well as the quality of teaching-learning and the state of preparedness for future education.